Influenza Vaccinationfor Health Care Workers: A Duty of Care - Pamela Orr (Canadian Journal of Infectious Diseases)
The medical literature has amply documented the transmission of influenza from patients to health care workers (HCWs) (1,2), from HCWs to patients (3) and between HCWs (4-9). The consequences of influenza transmission within the health care environment include morbidity and mortality among patients, most of who are at high risk for the complications of infection, and illness and absenteeism among health care providers. When outbreaks occur in health care facilities, absenteeism among HCWs may approach 30% to 40%, resulting in severe staff shortages, increased employment costs and the potential endangerment of health care delivery due to the scarcity of replacement workers (10-13).